2014
DOI: 10.1177/0148558x14521212
|View full text |Cite
|
Sign up to set email alerts
|

Are International Financial Reporting Standards–Based and U.S. GAAP–Based Accounting Amounts Comparable? Evidence From U.S. ADRs

Abstract: This article examines whether accounting amounts reported under International Financial Reporting Standards (IFRS) by firms cross-listed in the United States (American Depositary Receipts [ADRs]) are comparable with those reported under U.S. Generally Accepted Accounting Principles (GAAP). We compare the two samples on the basis of explanatory power of price, return, and cash flow models, timeliness in reporting, accrual quality, and predictive power of accounting. Value relevance, timeliness, and accrual qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“… Similarly, Eng, Sun, and Vichitsarawong () studied non‐U.S. firms with American Depository Receipts (ADRs) that were either required or permitted to adopt IFRS instead of U.S. GAAP and overall found insignificant differences in earnings attributes.…”
mentioning
confidence: 99%
“… Similarly, Eng, Sun, and Vichitsarawong () studied non‐U.S. firms with American Depository Receipts (ADRs) that were either required or permitted to adopt IFRS instead of U.S. GAAP and overall found insignificant differences in earnings attributes.…”
mentioning
confidence: 99%
“…Given the paper's similarity to these prior studies, particularly Eng et al (2014) and Landsman et al (2012), I would like to have seen more detailed discussion of why one might expect different results from these prior studies and how those expectations relate to differences in the research design choices.…”
Section: Incremental Contribution To the Literaturementioning
confidence: 97%
“…In general, prior research suggests that, when compared to firms using domestic accounting standards, firms using IFRS have higher-quality and more comparable financial reporting (see, e.g., Barth, Landsman, $_amp_$amp;Lang, 2008;Barth, Landsman, Lang, $_amp_$amp;Williams, 2012;Eng, Sun, $_amp_$amp;Vichitsarawong, 2014). In addition, Landsman, Maydew, and Thornock (2012) find that earnings disclosures for firms in IFRS-mandating countries were more informative (in terms of both prices and trading volume) than firms in domestic GAAP-using countries.…”
Section: Incremental Contribution To the Literaturementioning
confidence: 99%
“…Most of the countries have started to converge their local accounting standards with international standards early [36]. 4 For example, on November 2007 the Securities Exchange Commission (SEC) required foreign firms to use only IFRS in preparing their statements [22,37]. This change has taken place due to the joint efforts between IASB and U.S Financial Accounting Standard Board (FASB) to promote accounting standards universally [14,38].…”
Section: Adoption Of Accounting Standardsmentioning
confidence: 99%
“…This change has taken place due to the joint efforts between IASB and U.S Financial Accounting Standard Board (FASB) to promote accounting standards universally [14,38]. 5 In this context, Eng, Sun and Vichitsarawong [37] found that accounting figures that were reported using U.S. GAAP before 2007 were equivalent to those reported under IFRS after 2007. This modification has also taken place in European Union (EU) countries where the European 4 Convergence is "the process of narrowing differences between IFRS and the accounting standards of countries that retain their own standards" [2, p.9].…”
Section: Adoption Of Accounting Standardsmentioning
confidence: 99%